Predictive capability of the implicit theory of intelligence in the classroom interaction according to Flanders system among faculty staff at the Palestine Technical University – Khadouri - Ayyash, Wafaa Mahmood (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the predictive ability of the implicit theory of intelligence in classroom interaction according to the Flanders system among the sample of professors at the Technical University of Palestine - Khadouri, and to reveal the differences in the implicit theory of intelligence according to variables (gender, specialization, academic qualification, experience), and a sample consisting of 40 lecturers from Palestine Technical University, and the results of the study resulted in university professors viewing intelligence as incremental, and there are no statistically significant differences on the two dimensions of the implicit theory of intelligence scale due to variables of gender, specialization, academic qualification and experience. As for the experience variable, the result was in favor of the intelligence of being and the category of more than ten years. And that the classroom interaction was indirect, and that the perceptions of university professors contributed to predicting class interaction, as it had a predictive ability indicative of class interaction among faculty members at the university.
Keywords: Predictive capability of the implicit theory of intelligence; Classroom interaction